The RIIβ Regulatory Subunit of Protein Kinase A Binds to cAMP Response Element: An Alternative cAMP Signaling Pathway - Srivastava, Rakesh K.; Lee, Youl Nam; Noguchi, Kohei; Park, Yun Gyu; Matthew J. C. Ellis; Jeong, Jin-Sook; Kim, Se Nyun; Cho-Chung, Yoon S. (Proceedings of the National Academy of Sciences - PNAS, 1998)
cAMP, through the activation of cAMP-dependent protein kinase (PKA), is involved in transcriptional regulation. In eukaryotic cells, cAMP is not considered to alter the binding affinity of CREB/ATF to cAMP-responsive element (CRE) but to induce serine phosphorylation and consequent increase in transcriptional activity. In contrast, in prokaryotic cells, cAMP enhances the DNA binding of the catabolite repressor protein to regulate the transcription of several operons. The structural similarity of the cAMP binding sites in catabolite repressor protein and regulatory subunit of PKA type II (RII) suggested the possibility of a similar role for RII in eukaryotic gene regulation. Herein we report that RIIβ subunit of PKA is a transcription factor capable of interacting physically and functionally with a CRE. In contrast to CREB/ATF, the binding of RIIβ to a CRE was enhanced by cAMP, and in addition, RIIβ exhibited transcriptional activity as a Gal4-RIIβ fusion protein. These experiments identify RIIβ as a component of an alternative pathway for regulation of CRE-directed transcription in eukaryotic cells.